Eine Gebirglerin und die Wissenschaft – Josephine Kablik als prominente Wissenschaftlerin des Riesengebirges - Karel Stibral (Góry, Literatura, Kultura)
The chapter deals with the work of the scientist Josephine Kablik (Josefína Kablíková, née Ettel, 1787–1863), who worked in Vrchlabí (Hohenelbe) in the Czech (or Austrian) part of the Krkonoše Mountains. Kablik, who was born in the Giant Mountains (Krkonoše), became a leading botanist of the Austrian Empire, fundamental for the systematic knowledge of the Krkonoše flora. Although she remained in the mountains for most of her life, she maintained numerous correspondence with a number of scientific authorities, was a member of several scientific societies and supplied herbariums not only in Prague, but also in Austria, Germany and England. Among other things, she contributed a number of plants for the creation of the Herbarium Silesiacum of the Silesian Society for Patriotic Culture in Wrocław. Her activities also extended to other natural sciences, and at the same time she and her husband, a pharmacist, were active in charity work.